Teledentistry and COVID-19: Be Mindful of Bogus "Good" Ideas! - Nicolas Giraudeau DDS, PhD (SAGE Publishing, 2021)
The current health crisis has led to the emergence of new practices, new tools, and an increased use of digital health. Unfortunately, these are too often developed in a way that defies all logic or which has nothing to do with public health. Oral health professionals have been particularly affected during this crisis, and the use of digital health, and especially teledentistry, has been considered in many countries. However, the development of teledentistry is not free of bogus "good" ideas. It is time that teledentistry be adequately considered, while ensuring the quality of the medical procedure and with the aim of reducing inequalities in terms of access to oral healthcare and public health problems.